2003
DOI: 10.1029/2002ja009742
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary magnetic field control of polar patch velocity

Abstract: [1] Polar patch drift speed and direction have been investigated using oxygen 630 nm images recorded by an all-sky imager at Eureka (89°CGM), Canada over an extended period, January and December 1998. Statistical studies showed that (1) the interplanetary magnetic field (IMF, from the WIND satellite) B z component linearly controls the patch speed when B z is between À7.5 nT and 0 nT. The speed tends to saturate when B z is less than À7.5nT due to nonlinear coupling between the solar wind and the magnetosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
3
1
0
Order By: Relevance
“…This is in very good agreement with earlier observations [e.g., Cannon et al , ; Fukui et al , ; Zhang et al , ; Moen et al , ; Hosokawa et al , ; Yang et al , ]. The effect of IMF B y on the trajectory of patch material in the polar caps can be explained by the influence of IMF B y on the polar ionospheric convection and on poleward moving auroral forms [e.g., Heppner and Maynard , ; Zhang et al , ; Karlson et al , ; Ruohoniemi and Greenwald , ; Moen et al , ]. Indeed, for IMF B y <0, the cusp inflow region is shifted toward prenoon and the patch material will be pulled into the duskside.…”
Section: Discussionsupporting
confidence: 90%
“…This is in very good agreement with earlier observations [e.g., Cannon et al , ; Fukui et al , ; Zhang et al , ; Moen et al , ; Hosokawa et al , ; Yang et al , ]. The effect of IMF B y on the trajectory of patch material in the polar caps can be explained by the influence of IMF B y on the polar ionospheric convection and on poleward moving auroral forms [e.g., Heppner and Maynard , ; Zhang et al , ; Karlson et al , ; Ruohoniemi and Greenwald , ; Moen et al , ]. Indeed, for IMF B y <0, the cusp inflow region is shifted toward prenoon and the patch material will be pulled into the duskside.…”
Section: Discussionsupporting
confidence: 90%
“…This was due to strongly southward IMF B z and slightly negative IMF B y [Weimer, 1995]. Such convections are also consistent with the IMF dependence of polar ionospheric convection direction revealed by drifting of polar patches [Zhang et al, 2003]. The ionospheric convection patterns in Figure 6 indicate the plasma flow was roughly parallel to the red line in Figure 1b, indicating that the plasma and the magnetic fields in both ionosphere and magnetosphere were brought toward the nightside gap where reconnection occurred in the magnetotail and lead to polar rain electron energy dispersion.…”
Section: Eventsupporting
confidence: 86%
“…McEwen and Harris [1996] and Zhang et al [2003] documented an IMF B y control on azimuthal motion of the patches observed at Eureka station, ideally situated in the middle of the polar cap at Eureka (89°corrected geomagnetic latitude (CGM)), Canada, consistent with convection models developed by Weimer [1995] and Hairston and Heelis [1990]. Hosokawa et al [2009b] presented similar statistical results by applying automated patch detection and velocity determination procedures to all-sky airglow imager observations at Resolute Bay (83°CGM).…”
Section: Patch Transport Across the Polar Capsupporting
confidence: 62%